The Comparative Study of the Therapeutic Effects and Mechanism of Baicalin, Baicalein, and Their Combination on Ulcerative Colitis Rat - Liang, Shuai; Deng, Xin; Lei, Lei; Zheng, Yao; Ai, Jiao; Chen, Linlin; Xiong, Hui; Mei, Zhinan; Cheng, Yung-Chi; Ren, Yongshen (Frontiers in Pharmacology, 2019)
Introduction: Ulcerative colitis (UC) is an inflammatory bowel disease with a high incidence rate and a difficult treatment regimen. Recently, significant advances in the treatment of intestinal diseases, particularly UC, have been made with the use of the drugs baicalin and baicalein, separately or in combination. However, the therapeutic efficacy and mechanism of action of baicalin, baicalein, and their combination therapy, in the treatment of UC has not been fully elucidated. Materials and Methods: we constructed a UC rat model that encompassed a variety of complex factors, including a high-sugar and high-fat diet, a high temperature and humidity environment (HTHE), excess drinking, and infection of Escherichia coli. Model rats were then treated with baicalin, baicalein, or a combination of the two. Results: The results showed significant differences in the therapeutic effects of baicalin, baicalein, and the combination therapy, in the treatment of UC, as well as differences in the inhibition of inflammation via the nuclear factor-κB and MAPK pathways. The rat model of UC was established as described above. Then, the rats were treated for 7 days with baicalin (100 mg kg-1), baicalein (100 mg kg-1), or both (100 mg kg-1, baicalin: baicalein = 4:1/1:1). Clinical symptoms and signs, body temperature, organ indices, histopathology, blood biochemistry, and metabolites were examined to compare treatment effects and indicators of UC. Baicalin, YSR (Young Scutellaria baicalensis ratio of baicalin and baicalein), baicalein, and WSR (Withered Scutellaria baicalensis ratio of baicalin and baicalein) had significantly different effects in terms of clinical symptoms and signs, body temperature, organ indices, serum inflammatory cytokine levels, blood biochemistry, and histopathology changes in the main organs; YSR exhibited the best treatment effects. LC-MS/MS was used to detect the conversion of baicalin, baicalein, or both, into the six types of metabolites: baicalin, wogonoside, oroxin A, baicalein, wogonin, and oroxylin A. The levels of the six metabolites under the different treatment conditions were significantly different in the large intestine, small intestine, and lungs, but not in the blood. The levels of the six metabolites were significantly different in the large intestine, small intestine, and lung, but not in the serum. Conclusion: All these results indicate that baicalin and baicalein should be used more accurately in specific diseases, especially baicalin or high content of baicalin in Scutellaria baicalensis (Tiaoqin) should be preferred in treatment of UC.